Training in self-regulated learning based on a neuropsychological approach to academic stress in university students - Diego Daniel Díaz Guerra; Marena de la C Hernández Lugo; María del Pilar Fernández Celis; Raquel Yovana Tello Flores; Esteban Rodríguez Torres (Revista Información Científica)
Introduction: academic stress is a common challenge among university students and can have negative effects on their performance and well-being, as well as hinder conscious learning regulation. This article presents a training program designed to address this problem from a neuropsychological approach and promote self-regulated learning.